Politeness research: Key trajectories and their applicability in intercultural communication - Válková, Silvie (Linguistik Online, 2018)
With the plethora of studies on politeness in general and linguistic politeness in particular, it is difficult for those who want to apply the theoretical findings to authentic language data, to find a roadmap to theoretical framework on which to base the data processing and achieve relevant results. The pre-requisite for such objectives is the familiarity with the existing politeness theories of which to choose with a particular aim in mind, but since there are so many, also the knowledge of their potential taxonomies and the pros and cons of such taxonomies when applied to overt language manifestations of politeness (e. g. in addressing or apologizing). Consequently, the multiple aim of this study is to survey the approaches to the concept of politeness and its layering, outline the taxonomies of various approaches to polite-ness, and discuss the ways of their applicability (based on my hands-on experience with overt language manifestations of social deixis in addressing and strategies of apologizing). In the application section, the importance of a dynamic, context-sensitive approach to language data is advocated, followed by proposed changes in speech act taxonomies. The conclusion then sums up possible perspectives in intercultural communication which remain a challenge to new insights into politeness research and ELT methodology.